Dispersion-engineered silicon nitride waveguides for mid-infrared supercontinuum generation covering the wavelength range 0.8–6.5 μm - Ahmad, Harith; Karim, Mohammad Rezaul; Rahman, B.M. Azizur (IOP Publishing, 2019)
We numerically demonstrate the generation of a mid-infrared supercontinuum (SC) through the design of an on-chip complementary metal oxide semiconductor compatible 10 mm-long air-clad rectangular waveguide made using stoichiometric silicon nitride (Si3N4) as the core and MgF2 glass as the lower cladding. The proposed waveguide is designed for pumping in both the anomalous and all-normal dispersion regimes. A number of waveguide geometries are tailored for pumping at 1.55 μm with ultrashort pulses of 50 fs duration and a peak power of 5 kW. By initially keeping the thickness constant at 0.8 μm, four different structures are engineered with varying widths between 3 μm and 6 μm. The largest SC spectral evolution covering a region of 0.8 μm to beyond 6.5 m could be realized by a waveguide geometry with a width of 3 μm. Numerical analysis shows that increasing width beyond 3 μm while keeping thickness constant at 0.8 μm results in a reduction of the SC extension in the long wavelength side. However, the SC spectrum can be enhanced beyond 6.5 μm by increasing the waveguide thickness beyond 0.9 μm with the same peak power and pump source. To the best of our knowledge, this is the first report of a broad SC spectral evolution through numerical demonstration in the mid-infrared region by the Si3N4 waveguide. In the case of all-normal dispersion pumping, a flatter SC spectra can be predicted with the same peak power and pump pulse but with a reduced bandwidth spanning 950-2100 nm. © 2019 Astro Ltd.